Active energy ray-curable adhesive composition
The active energy ray curable adhesive composition, formulated with specific monomer ratios, addresses the issue of insufficient adhesion in aluminum laminate films by providing excellent bonding between aluminum foil and resin layers, including high-polarity materials like nylon.
Patent Information
- Application Number
- JP2023175805
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2043-10-11
AI Technical Summary
Existing active energy ray curable adhesive compositions for aluminum laminate films exhibit insufficient adhesion between the aluminum foil and the resin layer, particularly with high-polarity resin layers like nylon.
An active energy ray curable adhesive composition comprising 30.0 to 59.99% by mass of an amide group-containing monomer, 40.0 to 69.99% by mass of an aliphatic hydrocarbon group-containing monomer, and 0.01 to 10.0% by mass of a phosphate ester group-containing monomer, which is suitable for bonding aluminum foil to resin layers in aluminum laminate films.
The adhesive composition achieves excellent adhesion between the aluminum foil and the resin layers without aging, particularly improving the adhesion with highly polar resin films like nylon, and enhancing work efficiency in laminate production.
Smart Images

Figure 2025066313000001 
Figure 2025066313000002 
Figure 2025066313000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable adhesive composition, that is, an adhesive composition that can be cured by active energy rays. [Background technology]
[0002] Various proposals have been made as adhesives that can be cured by active energy rays (for example, electron beams or ultraviolet rays) (Patent Documents 1 to 8). Patent Documents 1 to 5 disclose active energy ray-curable adhesives that contain reactive prepolymers having radically polymerizable reactive groups. For example, Patent Document 1 discloses an electron beam-curable adhesive composition for lamination that contains polyurethane poly(meth)acrylate, and claims that the polyurethane poly(meth)acrylate improves the adhesive strength of the adhesive composition and improves the heat resistance of the cured product of the adhesive composition. Patent Documents 6 and 7 disclose active energy ray-curable adhesives that contain hydroxyl group-containing (meth)acrylate, and claim that an excellent adhesive can be provided without aging during adhesion. Patent Document 8 discloses a pressure-sensitive adhesive composition that can be cured by active energy rays and contains a polymerizable composition that contains N-substituted (meth)acrylamide.
[0003] Aluminum laminate films are also used as films for various packaging (for example, packaging films for light packaging, exterior films for batteries (lithium ion batteries, etc.)). The aluminum laminate film is a laminated film in which, for example, a stretched thermoplastic resin film such as a nylon resin layer, an aluminum foil layer, and a non-stretched thermoplastic resin film such as a polyolefin resin layer are laminated in this order, and has an adhesive layer that bonds the nylon resin layer and the aluminum foil layer, and an adhesive layer that bonds the aluminum foil layer and the polyolefin resin layer (see Patent Documents 9 and 10). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 6-184498 [Patent Document 2] Patent Publication No. 2000-17235 [Patent Document 3] Patent Publication No. 2015-13935 [Patent Document 4] Patent Publication No. 2021-165329 [Patent Document 5] Special table number 2017-538812 [Patent Document 6] Patent No. 7137726 [Patent Document 7] Patent No. 7137727 [Patent Document 8] Patent Publication No. 2023-123427 [Patent Document 9] Patent Publication No. 2007-73402 [Patent Document 10] JP2005-56729A Summary of the Invention [Problem to be solved by the invention]
[0005] As described above, in the aluminum laminate film, an aluminum foil and a resin layer laminated on both sides of the aluminum foil are laminated via an adhesive. This adhesive may be a thermosetting urethane adhesive, but if this adhesive is an active energy ray curing adhesive, it can be a solvent-free and VOC (volatile organic compound)-free adhesive, and it has the advantages of being aging-free, energy-free, improving the working environment, and improving the working efficiency in the production of the laminate.
[0006] The present inventors have found that conventional active energy ray-curable adhesive compositions do not provide sufficient adhesion between an aluminum foil and a resin layer in an aluminum laminate film, particularly between an aluminum foil and a highly polar resin layer such as a nylon resin (i.e., an aluminum laminate film having sufficient peel strength cannot be obtained). Therefore, the present invention provides an active energy ray-curable adhesive composition that can be used for bonding an aluminum foil and a resin layer and can be used in the production of an aluminum laminate film. [Means for solving the problem]
[0007] That is, the present invention relates to an active energy ray-curable adhesive composition as described below. [1] An active energy ray-curable adhesive composition comprising 30.0 to 59.99 mass% of an amide group-containing monomer (A), 40.0 to 69.99 mass% of an aliphatic hydrocarbon group-containing monomer (B), and 0.01 to 10.0 mass% of a phosphate ester group-containing monomer (C). [2] The active energy ray-curable adhesive composition according to [1] above, which is an electron beam-curable type.
[0008] Further, as a preferred embodiment, the present invention relates to the following active energy ray-curable adhesive composition. [3] The active energy ray-curable adhesive composition according to [1] or [2], wherein the aliphatic hydrocarbon group-containing monomer (B) is a (meth)acrylate having an aliphatic hydrocarbon group. [4] The active energy ray-curable adhesive composition according to any one of [1] to [3] above, wherein the aliphatic hydrocarbon group-containing monomer (B) is a monofunctional monomer. [5] The active energy ray-curable adhesive composition according to any one of [1] to [4] above, wherein the aliphatic hydrocarbon group-containing monomer (B) has an aliphatic hydrocarbon group having 8 to 30 carbon atoms. [6] The active energy ray-curable adhesive composition according to any one of [1] to [5] above, wherein the aliphatic hydrocarbon group-containing monomer (B) has an aliphatic hydrocarbon group having 10 to 18 carbon atoms. [7] The active energy ray-curable adhesive composition according to any one of [1] to [6] above, wherein the amide group-containing monomer (A) has a cyclic structure. [8] The active energy ray-curable adhesive composition according to any one of [1] to [7] above, wherein the amide group-containing monomer (A) has a morpholino group.
[0009] Furthermore, the present invention relates to an active energy ray-curable adhesive composition as a laminating adhesive, and a laminate, as described below. [9] The active energy ray-curable adhesive composition according to any one of the above [1] to [8], which is a lamination adhesive for laminating an aluminum foil and another layer.
[10] A laminate comprising an aluminum foil, paper or a resin film, and an adhesive layer which is a cured product of an active energy ray-curable adhesive composition that bonds the aluminum foil and the paper or the resin film; the active energy ray-curable adhesive composition comprising 30.0 to 59.99 mass% of an amide group-containing monomer (A), 40.0 to 69.99 mass% of an aliphatic hydrocarbon group-containing monomer (B), and 0.01 to 10.0 mass% of a phosphate ester group-containing monomer (C). Effect of the Invention
[0010] The active energy ray curable adhesive composition of the present invention can exhibit excellent adhesive properties in the adhesion process of the adherend without aging the adhesive layer before curing (applied adhesive coating film) and the adhesive layer after curing with active energy rays. In particular, the active energy ray curable adhesive composition of the present invention can be used as a lamination adhesive between aluminum foil and other layers (such as resin films), particularly aluminum foil and highly polar resin films, in the production of aluminum laminate films, and exhibits excellent adhesive properties.
[0011] Furthermore, in the production of an aluminum laminate film, when a non-polar resin film (such as a polyolefin film) is laminated on one side and a polar resin film (such as a nylon film) is laminated on the other side, the active energy ray-curable adhesive composition of the present invention can be used as a laminating adhesive for both sides, which can improve working efficiency, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] 1. Active energy ray-curable adhesive composition The active energy ray-curable adhesive composition (hereinafter also referred to as adhesive composition) of the present invention can contain an amide group-containing monomer (A), an aliphatic hydrocarbon group-containing monomer (B), a phosphate ester group-containing monomer (C), any other monomer (such as an oligomer), and, if necessary, any additives.
[0013] 1-1. Amide group-containing monomer (A) The amide group-containing monomer (A) is not particularly limited as long as it has an amide group and a functional group having polymerization reactivity with the active energy ray irradiated. The amide group-containing monomer (A) may be a monofunctional monomer having only one functional group having polymerization reactivity with the active energy ray, or a polyfunctional monomer having two or more functional groups, but is preferably a monofunctional monomer. The molecular weight of the amide group-containing monomer (A) is not particularly limited, but may be in the range of 60 to 400 (preferably 100 to 400, more preferably 120 to 400). In the active energy ray-curable adhesive composition of the present invention, an amide group-containing monomer (A) having too small a molecular weight is likely to have high reactivity with the phosphate ester group-containing monomer (C), and may be difficult to obtain stability as a composition. Therefore, it may be preferable that the amide group-containing monomer (A) has a molecular weight of a certain level or more.
[0014] The amide group-containing monomer (A) may be, for example, (meth)acrylamide (A-1), which is a reaction product of (meth)acrylic acid and an amine compound, or N-vinyl-amide compound (A-2). The amide group-containing monomer (A) preferably has a cyclic structure. For example, the (meth)acrylamide (A-1) is preferably a compound in which (meth)acrylic acid and a cyclic amine are amide-bonded. The N-vinyl-amide compound (A-2) is preferably a compound in which a vinyl group is bonded to the amide nitrogen atom of a cyclic amide compound.
[0015] Examples of (meth)acrylamide (A-1) include compounds that do not have a cyclic structure, such as dialkyl-substituted (meth)acrylamides, such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, and N,N-di(iso)propyl(meth)acrylamide; alkyl-substituted aminoalkyl(meth)acrylamides, such as N-ethyl-N-methylaminopropyl(meth)acrylamide and N,N-dimethylaminopropyl(meth)acrylamide; and compounds that have a cyclic structure, such as (meth)acryloylmorpholine, (meth)acryloylpyrrolidine, and (meth)acryloylpiperidine. The glass transition temperature (Tg) of the homopolymer of (meth)acrylamide (A-1) may be 100°C or higher, or 120°C or higher. For example, the Tg of the homopolymer of acryloylmorpholine is 145°C.
[0016] Examples of the N-vinyl-amide compound (A-2) include compounds that do not have a cyclic structure, such as N-vinylformamide, N-vinylacetamide, N-vinylisopropylamide, and N-vinyl-N-methylacetamide; those that have a cyclic structure include N-vinylpyrrolidone and N-vinylcaprolactam.
[0017] The content of the amide group-containing monomer (A) in the adhesive composition is 30.0% by mass or more, preferably 35.0% by mass or more, and more preferably 40.0% by mass or more; on the other hand, it is 59.99% by mass or less, preferably 55.0% by mass or less, and more preferably 50.0% by mass or less. The amide group-containing monomer (A) tends to have high polarity and has high affinity with highly polar resins such as polyamide resins (nylon, etc.). Therefore, the adhesive composition containing the amide group-containing monomer (A) tends to increase the adhesive strength between the polyamide resin film and other layers. On the other hand, the amide group-containing monomer (A) tends to have a high glass transition temperature, so that the cured product of the adhesive composition having a too high content of the amide group-containing monomer (A) may be brittle.
[0018] 1-2. Aliphatic hydrocarbon group-containing monomer (B) The aliphatic hydrocarbon group-containing monomer (B) is a monomer compound containing an aliphatic hydrocarbon group and a functional group capable of radical polymerization by active energy rays. The aliphatic hydrocarbon group-containing monomer (B) may be a monofunctional monomer having only one group capable of radical polymerization by active energy rays, or a polyfunctional monomer having two or more groups, but is preferably a monofunctional monomer. The molecular weight of the aliphatic hydrocarbon group-containing monomer (B) is not particularly limited, but may be in the range of 100 to 500. In addition, it may be preferable that the aliphatic hydrocarbon group-containing monomer (B) is liquid at room temperature (for example, 25°C) (has a melting point below room temperature). The aliphatic hydrocarbon group-containing monomer (B) that is solid at room temperature may solidify (crystallize) in the adhesive composition, which may reduce the adhesiveness of the adhesive.
[0019] The aliphatic hydrocarbon group contained in the aliphatic hydrocarbon group-containing monomer (B) may be linear, cyclic, or branched. The aliphatic hydrocarbon group may be a saturated or unsaturated hydrocarbon group, but is preferably a saturated aliphatic hydrocarbon group. The aliphatic hydrocarbon group contained in the aliphatic hydrocarbon group-containing monomer (B) preferably has 8 to 30 carbon atoms, preferably has 10 to 18 carbon atoms, and more preferably is a lauryl group (12 carbon atoms) or an (iso)decyl group (10 carbon atoms). The higher the carbon number of the aliphatic hydrocarbon group in the aliphatic hydrocarbon group-containing monomer (B), the higher its hydrophobicity. Therefore, it is preferable to adjust the carbon number of the aliphatic hydrocarbon group according to the degree of hydrophobicity required for the aliphatic hydrocarbon group-containing monomer (B).
[0020] The aliphatic hydrocarbon group-containing monomer (B) is typically a (meth)acrylic ester having an aliphatic hydrocarbon group in the ester moiety. A typical example of the (meth)acrylic ester having an aliphatic hydrocarbon group in the ester moiety is an alkyl (meth)acrylate. The alkyl (meth)acrylate may be a chain alkyl (meth)acrylate or a cyclic alkyl (meth)acrylate.
[0021] Examples of linear alkyl (meth)acrylates include decyl (meth)acrylate, dodecyl (meth)acrylate, isooctyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isodecyl (meth)acrylate, isomyristyl (meth)acrylate, octadecyl (meth)acrylate, dicyclopentanyl (meth)acrylate, tridecyl (meth)acrylate, nonyl (meth)acrylate, hexadecyl (meth)acrylate, myristyl (meth)acrylate, isobornyl (meth)acrylate, etc. Examples of cyclic alkyl (meth)acrylates include dicyclopentenyl (meth)acrylate, 1-adamantyl (meth)acrylate, 3,5,5-trimethylcyclohexyl (meth)acrylate, 4-t-butylcyclohexyl (meth)acrylate, etc.
[0022] The aliphatic hydrocarbon group-containing monomer (B) may be an aliphatic hydrocarbon group-containing monomer using a biomass-derived material. For example, it is a (meth)acrylate obtained by esterifying (meth)acrylic acid with a higher alcohol derived from vegetable oil. Examples of vegetable oil include palm oil, palm kernel oil, coconut oil, etc., which contain higher alcohols. Higher alcohols derived from vegetable oils generally have 10 to 20 aliphatic hydrocarbon groups. Lauryl acrylate and the like are commercially available as (meth)acrylates obtained by esterifying (meth)acrylic acid with higher alcohols derived from vegetable oils. By using such a biomass-derived material, the environmental load can be reduced.
[0023] The content of the aliphatic hydrocarbon group-containing monomer (B) in the adhesive composition is 40.0 mass% or more, preferably 45.0 mass% or more, and 69.99 mass% or less, preferably 60.0 mass% or less. An adhesive composition containing an appropriate amount of the aliphatic hydrocarbon group-containing monomer (B) tends to have high adhesive performance, particularly adhesive performance between an aluminum foil and a non-polar resin layer.
[0024] 1-3. Phosphate-containing monomer (C) The phosphate ester group-containing monomer (C) may be a monomer compound having a phosphate ester group and a functional group having polymerization reactivity with respect to the active energy ray irradiated. The phosphate ester group-containing monomer (C) may be a monofunctional monomer having only one functional group having polymerization reactivity, or a polyfunctional monomer having two or more functional groups; however, it is preferably a polyfunctional monomer, and it is preferable that it has two or three functional groups having polymerization reactivity, and more preferably has two functional groups. This is because the phosphate ester group-containing monomer (C) acts as a crosslinking agent.
[0025] The phosphate ester group-containing monomer (C) is preferably, for example, a phosphate ester (meth)acrylate having both a phosphate ester group and a (meth)acryloyl group in the molecule. That is, a phosphate ester (meth)acrylate is a compound in which a "functional group containing a (meth)acryloyl group" is introduced into one, two or three of the three -OH groups of phosphoric acid (P(=O)(OH)3), and can be represented by the following formula. The substituents R(1a), R(2a), R(2b), R(3a), R(3b), and R(3c) in the following formula are each independently a "functional group containing a (meth)acryloyl group". The (meth)acryloyl group means a methacryloyl group or an acryloyl group. [ka]
[0026] In the above formula, the substituents R(1a), R(2a), R(2b), R(3a), R(3b), and R(3c) each independently represent a "functional group containing a (meth)acryloyl group" (functional groups having the same or different structures), and examples of the functional group containing a (meth)acryloyl group include groups represented by the following formulas. In the following formulas, R represents a hydrogen atom or a methyl group, R1 represents an alkylene group (preferably an alkylene group having 1 to 4 carbon atoms), and R2 represents an alkylene group (preferably an alkylene group having 1 to 10 carbon atoms). [ka]
[0027] A preferred example of the "functional group containing a (meth)acryloyl group" in the phosphate ester (meth)acrylate is a ((meth)acryloyloxy)alkyl group; examples of the ((meth)acryloyloxy)alkyl group include a (2-(meth)acryloyloxy)ethyl group, a (3-(meth)acryloyloxy)propyl group, and the like.
[0028] Further specific examples of phosphate ester (meth)acrylates include the following: [ka]
[0029] [ka]
[0030] [ka] (l, m, and n each independently represent 1 or 2).
[0031] The phosphate group-containing monomer (C) may be a commercially available product available on the market, and examples thereof include Sartomer SR9050 (2-(methacryloyloxy)ethyl phosphate, Sartomer Co., Ltd.), Sartomer SR9051 (bis[2-(methacryloyloxy)ethyl] phosphate, Sartomer Co., Ltd.), Sartomer SR9053 (tris[2-(acryloyloxy)ethyl] phosphate, Sartomer Co., Ltd.), Sartomer SR9051NS (Sartomer Co., Ltd.), Light Acrylate P-1A(N) (2-acryloyloxyethyl phosphate, Kyoeisha Chemical Co., Ltd.), Light Ester P-1M (2-(methacryloyloxy)ethyl phosphate, Kyoeisha Chemical Co., Ltd.), Light Ester P-2M (bis[2-(methacryloyloxy)ethyl] phosphate, Kyoeisha Chemical Co., Ltd.), EBECRYL168 (Daicel Allnex Co., Ltd.), and EBECRYL170 (Daicel Allnex Co., Ltd.).
[0032] The content of the phosphate ester group-containing monomer (C) in the adhesive composition is 0.01% by mass or more, preferably 0.1% by mass or more, and more preferably 1.0% by mass or more; on the other hand, it is 10.0% by mass or less, and more preferably 8.0% by mass or less. The phosphate ester group-containing monomer (C) tends to have high polarity, so that the adhesive composition containing the phosphate ester group-containing monomer (C) can exhibit high adhesion, particularly when the adherend is a polar resin film.
[0033] 1-4. Optional Other Ingredients The active energy ray-curable adhesive composition of the present invention may contain any other components, for example additives such as other monomers such as reactive prepolymers (reactive oligomers), surfactants, polymerization initiators, organic solvents, pigments or dyes, surface conditioners, light stabilizers, surface treatment agents, antioxidants, antiaging agents, crosslinking accelerators, plasticizers, ultraviolet absorbers, antifungal agents, preservatives, defoamers, and moisturizers.
[0034] 1-4-1. Reactive prepolymer The reactive prepolymer is an oligomer having a reactive functional group such as a carboxylic acid group, a hydroxyl group, or a urethane group. The reactive prepolymer may enhance the curing property of the adhesive composition. In particular, an adhesive composition that is cured by an electron beam as an active energy ray may be cured quickly by irradiation with an electron beam if it contains a reactive prepolymer. However, the reactive prepolymer may affect the physical properties of the cured product of the adhesive composition, and may reduce the adhesiveness. Examples of reactive prepolymers that can be blended include styrene acrylic oligomers, amine-modified (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyester (meth)acrylate oligomers, polyurethane (meth)acrylate oligomers, other oligomers, and polyalkylene glycol (meth)acrylates.
[0035] The amine-modified (meth)acrylate oligomer is an oligomer having at least one amino group and at least one (meth)acryloyl group in the molecule. The number of (meth)acryloyl groups in the amine-modified (meth)acrylate oligomer is preferably 1 to 6, more preferably 2 to 4, and particularly preferably has two (meth)acryloyl groups in the molecule. By adjusting the number of (meth)acryloyl groups in the amine-modified (meth)acrylate oligomer, the amine-modified (meth)acrylate oligomer becomes more likely to react with other polymerizable compounds.
[0036] The amine-modified (meth)acrylate oligomer may be a synthetic product obtained by polymerizing a desired monomer, or may be a commercially available product. Commercially available examples of the amine-modified (meth)acrylate oligomer include GENOMER5161 and GENOMER5275 (RAHN); CN371, CN371NS, CN373, CN383, CN384, CN386, CN501, CN503, CN550, and CN551 (Sartomer); EBECRYL80, EBECRYL81, EBECRYL83, EBECRYL7100, EBECRYL84, and EBECRYLP115 (Daicel-Allnex); Laromer PO 83F, Laromer PO 84F, Laromer LR8946, Larmer LR8956, Laromer LR8996, and Laromer LR8894 (BASF); and AgiSyn001, AgiSyn002, AgiSyn003, and AgiSyn008 (DSM Coating Resin); Photomer 4771, Photomer 4775, Photomer 4967, Photomer 5096, Photomer 5662, Photomer 5930 (Cognis); Doublecure EPD, Doublecure OPD, Doublecure 115, Doublecure 225, Doublecure 645, PolyQ222, PolyQ226, PolyQ224, PolyQ101 (DoubleBond Chemicals).
[0037] Examples of the polyalkylene glycol (meth)acrylate include polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, polypropylene glycol di(meth)acrylate, and the like.
[0038] The amount of reactive prepolymer contained in the adhesive composition is not particularly limited, but is usually 30% by mass or less, and often 20% by mass or less; in some cases, not including the reactive prepolymer may result in higher adhesiveness.
[0039] 1-4-2.Surfactants The active energy ray curable adhesive composition of the present invention may contain a surfactant. Examples of the surfactant include polyether-modified siloxane, fluorine-based surfactant, silicone-based surfactant, acetylene glycol or acetylene alcohol-based surfactant, etc. The polyether-modified siloxane is a surfactant obtained by modifying polysiloxane with polyether, and has a structure in which the side chain and / or terminal hydrocarbon group of silicone oil is replaced with a polyether group. The content of the surfactant in the adhesive composition is not particularly limited, but is usually 10% by mass or less, and often 5% by mass or less.
[0040] 1-4-3. Polymerization initiator When the active energy ray-curable adhesive composition of the present invention is an adhesive composition cured by ultraviolet light, it preferably contains a polymerization initiator. On the other hand, an adhesive composition cured by electron beams does not need to contain a polymerization initiator, and the absence of a polymerization initiator may result in higher adhesive strength.
[0041] Examples of the polymerization initiator include, but are not limited to, acylphosphine oxide compounds, triazine compounds, aromatic ketone compounds, aromatic onium salt compounds, organic peroxides, thioxanthone compounds, thiophenyl compounds, anthracene compounds, hexaarylbisimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, halogenated hydrocarbon compounds, alkylamine compounds, iodonium salt compounds, and sulfonium salt compounds.
[0042] 1-4-4.Solvent The active energy ray-curable adhesive composition of the present invention may contain an organic solvent, but the amount is preferably small (for example, 3 mass % or less relative to the adhesive composition), or preferably does not contain an organic solvent. Examples of the organic solvent include monoalcohols, polyhydric alcohols, lower alkyl ethers of polyhydric alcohols, ketones, ethers, esters, nitrogen-containing compounds, etc.
[0043] 1-5. Properties of active energy ray-curable adhesive composition The viscosity of the adhesive composition is preferably adjusted in consideration of workability, in accordance with the application method and the specifications of the coater when applying to the adherend. Although not particularly limited, the viscosity measured at 25°C (for example, measured according to JIS K 6833) is in the range of 50 to 5,000 mPa s, and may be in the range of 100 to 3,000 mPa s.
[0044] 1-6. Manufacturing method of active energy ray curable adhesive composition The active energy ray-curable adhesive composition of the present invention can be obtained by mixing the components in any order according to the formulation. If necessary, it can be heated, and the heating temperature may be appropriately set according to the composition used, the base material, the purpose, etc., but is, for example, 30 to 80°C.
[0045] 2.Laminate The active energy ray curable adhesive composition of the present invention can be used as an adhesive for bonding each layer in the production of a laminate. The layer to be bonded in the laminate is a resin layer, a metal layer, a paper layer, etc., and is not particularly limited. Although not particularly limited, the active energy ray curable adhesive composition of the present invention can be used as a lamination adhesive for laminating an aluminum foil and another layer (especially a resin layer).
[0046] The resin of the resin layer in the laminate may be a polar resin or a non-polar resin. The active energy ray curable adhesive composition of the present invention can exhibit excellent adhesion to any resin. Examples of the resin include polyolefin resin (polyethylene, polypropylene, ethylene-propylene copolymer, etc.), polyester resin (polyethylene terephthalate, polybutylene terephthalate, etc.), polyamide resin (nylon 6, nylon 66, nylon 11, nylon 12, etc.), polyvinyl chloride, polyvinyl acetate, polyvinyl alcohol, polystyrene, ABS resin (acrylonitrile-butadiene-styrene copolymer), polycarbonate, polyamideimide, polyimide, epoxy resin, phenolic resin, melamine resin, urethane resin, etc. The resin layer in the laminate may be stretched or not (unstretched).
[0047] Examples of metals for the metal layers in the laminate include aluminum, zinc, copper, iron, tin, etc., with aluminum being preferred.
[0048] The paper layer in the laminate can be synthetic paper, art paper, coated paper, cast paper, wood paper, resin-laminated paper, metal-vapor-deposited paper, metal oxide-vapor-deposited paper, or the like.
[0049] 2-1.Aluminum laminate film The active energy ray curable adhesive composition of the present invention can be used to prepare a laminate, but is preferably used to prepare an aluminum laminate film. The aluminum laminate film is a film in which paper, a resin film, or the like is laminated on one or both sides of an aluminum foil. The aluminum foil and the paper or resin film are bonded by an adhesive layer which is a cured product of the active energy ray curable adhesive composition of the present invention. The aluminum laminate film is a laminate in which a base film, an aluminum foil, and a sealing film are laminated in this order, although it is not particularly limited; it has an adhesive layer that bonds the base film and the aluminum foil, and an adhesive layer that bonds the aluminum foil and the sealing film. The aluminum laminate film may further have an additional layer.
[0050] The base film in the aluminum laminate film is not particularly limited, but is preferably a stretched thermoplastic resin film, and may be, for example, nylon resin, polyethylene terephthalate resin, polypropylene resin, etc. Stretched thermoplastic resin films made of these resins increase the mechanical strength of the laminate film and improve its processability. The thickness of the base film is not particularly limited, but may be in the range of 10 to 50 μm. If the thickness of the base film is low, the formability of the laminate film is likely to decrease. The surface of the base film (the surface facing the aluminum foil) may be modified by corona treatment or plasma treatment to increase wettability.
[0051] The aluminum constituting the aluminum foil in the aluminum laminate film may be an aluminum alloy containing Fe, Si, Mn, etc. The thickness of the aluminum foil is not particularly limited and varies depending on the application of the laminate film, but from the viewpoint of the formability of the laminate film and its barrier property, it is preferable that the aluminum foil has a thickness of 5 to 100 μm.
[0052] One or both surfaces of the aluminum foil in the aluminum laminate film may be surface-treated. The surface treatment can increase the peel strength between the aluminum foil and the base film and / or the sealant film. The surface treatment is, for example, a chemical conversion coating treatment of the surface of the aluminum foil with an electrolyte or the like, but is not particularly limited.
[0053] The sealant film in the aluminum laminate film is not particularly limited, but is preferably a non-stretched thermoplastic resin film, and may be, for example, a polyolefin resin (such as a polypropylene resin or a polyethylene resin) or an ionomer resin. The thickness of the sealant film is not particularly limited, but in consideration of the formability of the aluminum laminate film, it is preferable that the thickness is 10 to 100 μm. The surface of the sealant film (the surface facing the aluminum foil) may also be modified by corona treatment or plasma treatment, as in the case of the base film, to enhance wettability. The sealant film in the aluminum laminate film can be molded into a package by heat sealing (thermal fusion) the sealant films together.
[0054] The total thickness of the aluminum laminate film varies depending on the use of the film, but is generally 250 μm or less, and can be 150 μm or less.
[0055] The aluminum laminate film has an adhesive layer X that bonds the aluminum foil to the base film, and an adhesive layer Y that bonds the aluminum foil to the sealant film, and either or both of the adhesive layer X and the adhesive layer Y are cured products of the active energy ray-curable adhesive composition of the present invention. By making the adhesive layer X and the adhesive layer Y the cured products of the active energy ray-curable adhesive composition of the present invention, the adhesive strength between the aluminum foil and the base film and / or the sealant film can be increased; in particular, by making the adhesive layer X the active energy ray-curable adhesive composition of the present invention, the adhesive strength between the aluminum foil and the base film (particularly a highly polar resin film such as a nylon resin film) can be increased.
[0056] Either the adhesive layer X or the adhesive layer Y may be formed of an adhesive other than the active energy ray curable adhesive composition of the present invention. The adhesive other than the active energy ray curable adhesive composition of the present invention is preferably an active energy ray curable adhesive, but may be a thermosetting adhesive. The thermosetting adhesive may be a known urethane adhesive.
[0057] 2-2. Manufacturing method of laminate The laminate of the present invention (e.g., aluminum laminate film) can be produced by any method, typically comprising the steps of A) applying the active energy ray-curable adhesive composition of the present invention to the surface of one of the adherends, B) superposing the adhesive-coated surface of one of the adherends on another adherend to form a laminate, and C) irradiating the laminate with active energy rays to cure the applied adhesive.
[0058] A) To apply the active energy ray curable adhesive composition of the present invention to the surface of one of the adherends, the composition is applied by a known application means (spray application, roll application, solid printing, etc.) to form a coating layer. The coated surface of the adherend may be subjected to a known surface treatment or chemical treatment, and it may be preferable to perform a treatment such as corona treatment to increase the wettability of the coated surface of the adherend to the adhesive composition. In addition, the coated surface of the adherend may or may not be subjected to printing, painting, vapor deposition, etc.
[0059] The amount of the active energy ray-curable adhesive composition of the present invention applied to the adherend is 1.50 g / m2 in terms of the applied solid content in order to obtain excellent adhesive strength. 2 More than 1.80 g / m is preferable. 2 More preferably, 2.00 g / m or more 2 The above is more preferable.
[0060] When a metal foil (such as aluminum foil) is to be bonded to a resin film, as in the case of an aluminum laminate film, it is preferable to apply an active energy ray-curable adhesive composition to the resin film.
[0061] B) The step of laminating the adhesive-coated surface of one adherend with another adherend to form a laminate may be carried out, for example, using a normal dry laminating machine. Furthermore, before laminating, the adhesive applied to the adherends may be aged, but this is not necessary.
[0062] C) In the step of irradiating the laminate with active energy rays to cure the applied adhesive, the dose of active energy rays may be set so that the applied adhesive can be cured; in the case of irradiating with electron beams, the dose is preferably 10 kGy or more, more preferably 100 kGy or more; and preferably 500 kGy or less, more preferably 300 kGy or less. In the case of irradiating with ultraviolet rays, the dose is, for example, 400 mJ / cm. 2 The above is preferred.
[0063] In particular, to produce an aluminum laminate film using the active energy ray-curable adhesive composition of the present invention, for example, the following steps may be taken: 1) the active energy ray-curable adhesive composition of the present invention is applied to the surface of a base film and the surface of a sealant film to form an adhesive coating layer; 2) the adhesive coating layer of the base film is superimposed on one surface of an aluminum foil, and the adhesive coating layer of the sealant film is superimposed on the other surface of the aluminum foil to form a laminated film; and 3) the laminated film is irradiated with active energy rays from both the base film side and the sealant film side to cure the adhesive coating film.
[0064] 2-3. Uses of aluminum laminate film The laminate of the present invention (for example, an aluminum laminate film) can be used for any application, such as food packages, pouches for lithium ion batteries, sheets for building materials, and other laminate applications. EXAMPLES
[0065] A. Preparation of active energy ray-curable adhesive composition To prepare an active energy ray-curable adhesive composition, the following components were prepared. A-1. Amide group-containing monomer Acryloylmorpholine N-Vinylformamide A-2. Aliphatic hydrocarbon group-containing monomer Isodecyl acrylate Lauryl acrylate ·Stearyl acrylate A-3. Phosphate-containing monomer SR9051NS (Sartomer, bifunctional) A-4. Other monomers (bifunctional) ·PEG200DA (Polyethylene glycol 200 diacrylate) ·PEG400DA (Polyethylene glycol 400 diacrylate) ·PEG600DA (Polyethylene glycol 600 diacrylate) A-5. Reactive prepolymer CN371 (Sartomer, amine-modified (meth)acrylate oligomer) A-6. Surfactants Tego Glide 450 (Evonik, polyether modified siloxane copolymer)
[0066] The components were mixed according to the formulations shown in Tables 1 and 2 to obtain active energy ray-curable adhesive compositions.
[0067] B. Preparation of Laminate To prepare a laminate (aluminum laminate film), the following were prepared: Base film: Emblem (registered trademark) ONM, Unitika Co., Ltd., thickness 15 μm (corona surface treated easy-adhesion biaxially stretched nylon film) Aluminum foil: 9μm thick Sealant film: TUX (registered trademark)-HC, Mitsui Chemicals Tocello, thickness 50 μm (LLDPE (linear low density polyethylene) film)
[0068] An active energy ray curable adhesive composition was applied to the corona surface-treated surface of the base film (EMBLEM ONM) using a mere bar (0.3 mm). Without aging the coating film, aluminum foil was laminated onto the coating surface to produce laminate A. In addition, an active energy ray curable adhesive composition was applied to the surface-treated surface of the sealant film (TUX-HC) using a mere bar (0.3 mm). Without aging the coating film, the coating surface of the sealant film was laminated onto the aluminum foil side of the laminate A to produce laminate B consisting of "base film / adhesive coating layer / aluminum foil / adhesive coating layer / sealant film".
[0069] The laminate B thus produced was irradiated with electron beams from both the base film side and the sealant film side to cure the adhesive and produce a laminate. The electron beam was irradiated five times (quintuple irradiation) using an electron beam irradiation device (Iwasaki Electric Co., Ltd.) under conditions of an exposure dose of 30 kGy and 90 kV.
[0070] In this embodiment, the base film and the aluminum foil are laminated together, and then the sealant film is laminated thereon, but the order is not particularly limited. For example, the sealant film and the aluminum foil may be laminated together, and then the base film may be laminated thereon; the sealant film, the aluminum foil, and the base film may be laminated together at the same time.
[0071] C. Evaluation of Laminates Immediately after the laminate was produced, the adhesiveness was evaluated according to the following procedure. Using a tensile tester (Yasuda Seiki Seisakusho Co., Ltd.), the laminate was pulled in a 180° direction at a measurement temperature of 25° C. and a pulling speed of 200 mm / min, and the strength at break was obtained. The peel strength (T-type peel strength (g / 15 mm)) between the base film and the aluminum foil, and the peel strength (T-type peel strength (g / 15 mm)) between the sealant film and the aluminum foil were measured, and the adhesiveness (base) and adhesiveness (sealant) were evaluated according to the following criteria. ◎: Peel strength is 100g / 15mm or more ○: Peel strength is 50g / 15mm or more and less than 100g / 15mm △: Peel strength is 10g / 15mm or more and less than 50g / 15mm ×: Peel strength is less than 10g / 15mm
[0072] [Table 1]
[0073] [Table 2]
[0074] Comparative Examples 1 to 7 in Table 2 are all examples that do not contain SR9051NS, which is the phosphate group-containing monomer (C).
[0075] First, in Comparative Example 6, which does not contain the phosphate group-containing monomer (C) and contains the same mass of acryloylmorpholine as the amide group-containing monomer (A) and lauryl acrylate as the aliphatic hydrocarbon group-containing monomer (B), the adhesion to the sealant film (low-density polyethylene film) was sufficient, but the adhesion to the base film (nylon resin film) was insufficient. In contrast, in Examples 2 and 3, which contain the phosphate group-containing monomer (C) and contain (almost) the same mass of acryloylmorpholine and lauryl acrylate, the adhesion to both the base film and the sealant film was sufficient. In other words, it is suggested that the phosphate group-containing monomer (C) greatly contributes to improving the adhesion to the base film (nylon resin film) without deteriorating the adhesion to the sealant film.
[0076] On the other hand, in Comparative Example 1, which is composed of amine-modified oligomer CN371, acryloylmorpholine, lauryl acrylate, and surfactant Tego Glide 450 instead of phosphate ester group-containing monomer (C), adhesion to the base film was slightly improved but adhesion to the sealant film was significantly deteriorated compared to Comparative Example 6. It is clear that although the amine-modified oligomer may act as a crosslinking agent like the phosphate ester group-containing monomer (C), its improving effect on adhesion is insufficient.
[0077] In Comparative Example 3, which did not contain either the amide group-containing monomer (A) or the phosphate group-containing monomer (C) and was composed of lauryl acrylate, an amine-modified oligomer, and a surfactant, and in Comparative Example 4, which was composed of lauryl acrylate and a surfactant, the adhesion to both the base film and the sealant film was insufficient. Thus, it is clear that the combination of the amide group-containing monomer (A) and the phosphate group-containing monomer (C) is important for improving adhesion.
[0078] Furthermore, Comparative Example 2, which does not contain either the aliphatic hydrocarbon group-containing monomer (B) or the phosphate group-containing monomer (C) and is composed of acryloylmorpholine, an amine-modified oligomer, and a surfactant, had insufficient adhesion to the base film and adhesion to the sealant film. On the other hand, Comparative Example 5, which does not contain either the aliphatic hydrocarbon group-containing monomer (B) or the phosphate group-containing monomer (C) and is composed of acryloylmorpholine and a surfactant, had sufficient adhesion to the base film but insufficient adhesion to the sealant film. From this, it can be seen that the incorporation of the amine-modified oligomer can be a factor that deteriorates adhesion. The reason is not limited, but it may be because the cured product of acryloylmorpholine tends to be relatively brittle, and the brittleness of the cured product is further increased by combining it with the amine-modified oligomer.
[0079] Comparative Example 7 has a composition in which the amide group-containing monomer (A) acryloylmorpholine in Comparative Example 6 is changed to N-vinylformamide. Similar to Comparative Example 6, Comparative Example 7 had sufficient adhesion to the sealant film (low-density polyethylene film), but insufficient adhesion to the base film (nylon resin film).
[0080] In Comparative Example 8, the adhesive was composed only of a phosphate group-containing monomer (C), but the adhesion to both the base film and the sealant film was insufficient.
[0081] Comparative Examples 9 to 11 are examples in which polyethylene glycol diacrylate was blended.
[0082] Comparative Examples 9 and 10 are adhesives that do not contain an aliphatic hydrocarbon group-containing monomer (B) and are made of acryloylmorpholine, which is an amide group-containing monomer (A), SR9051NS, which is a phosphate group-containing monomer (C), and a surfactant; however, the adhesiveness to the sealant film, etc. was insufficient. This suggests that lauryl acrylate (the aliphatic hydrocarbon group-containing monomer (B)) contributes particularly to the improvement of the adhesiveness to the sealant film (low-density polyethylene film).
[0083] Comparative Example 11 is an example containing acryloylmorpholine, which is an amide group-containing monomer (A), lauryl acrylate, which is an aliphatic hydrocarbon group-containing monomer (B), and SR9051NS, which is a phosphate group-containing monomer (C), but with a slightly low content of acryloylmorpholine. In Comparative Example 11, adhesion to the sealant film was obtained to a certain extent, but adhesion to the base film (nylon resin film) was insufficient. This suggests that acryloylmorpholine contributes particularly to adhesion to the base film.
[0084] Examples 1 to 5 are examples containing a predetermined amount of acryloylmorpholine, which is an amide group-containing monomer (A), lauryl acrylate, which is an aliphatic hydrocarbon group-containing monomer (B), and SR9051NS, which is a phosphate group-containing monomer (C). In all of Examples 1 to 3, the adhesion to the base film and the adhesion to the sealant film were sufficient. However, it can be seen that the adhesion of Example 1, which contains an amine-modified oligomer, is somewhat reduced.
[0085] In addition, Example 4, in which the aliphatic hydrocarbon group-containing monomer (B) was isodecyl acrylate, and Example 5, in which stearyl acrylate was used, both had sufficient adhesion to the base film and to the sealant film. Example 5 showed a tendency for adhesion to the base film to decrease slightly, and the reasons for this are not limited to the following: stearyl acrylate is a solid at room temperature, and may solidify (crystallize) in the adhesive or in the coating film after curing; and, since it has a relatively low polarity among the aliphatic hydrocarbon group-containing monomers (B), it has a low compatibility with the amide group-containing monomer (A), which is particularly highly polar in the adhesive composition, compared to isodecyl acrylate and the like. [Industrial Applicability]
[0086] By using the active energy ray-curable adhesive composition of the present invention, it is possible to produce a ramnate film in which an aluminum foil and a resin film are firmly bonded; moreover, the production of the film has the advantages of being aging-free, energy-less, improving the working environment, and increasing the working efficiency.
Claims
1. 30.0 to 59.99% by mass of an amide group-containing monomer (A); 40.0 to 69.99 mass% of an aliphatic hydrocarbon group-containing monomer (B); and 0.01 to 10.0% by mass of a phosphate ester group-containing monomer (C), An active energy ray-curable adhesive composition.
2. The active energy ray-curable adhesive composition according to claim 1 , which is an electron beam-curable adhesive composition.
3. 2. The active energy ray-curable adhesive composition according to claim 1, wherein the aliphatic hydrocarbon group-containing monomer (B) is a (meth)acrylate having an aliphatic hydrocarbon group.
4. The active energy ray-curable adhesive composition according to claim 1 , wherein the aliphatic hydrocarbon group-containing monomer (B) is a monofunctional monomer.
5. 4. The active energy ray-curable adhesive composition according to claim 1, wherein the aliphatic hydrocarbon group-containing monomer (B) has an aliphatic hydrocarbon group having 8 to 30 carbon atoms.
6. 4. The active energy ray-curable adhesive composition according to claim 1, wherein the aliphatic hydrocarbon group-containing monomer (B) has an aliphatic hydrocarbon group having 10 to 18 carbon atoms.
7. The active energy ray-curable adhesive composition according to claim 1 , wherein the amide group-containing monomer (A) has a cyclic structure.
8. The active energy ray-curable adhesive composition according to claim 1 , wherein the amide group-containing monomer (A) has a morpholino group.
9. 3. The active energy ray-curable adhesive composition according to claim 1, which is a lamination adhesive for laminating an aluminum foil and another layer.
10. A laminate comprising an aluminum foil, paper or a resin film, and an adhesive layer that is a cured product of an active energy ray-curable adhesive composition that bonds the aluminum foil and the paper or the resin film, The active energy ray-curable adhesive composition is a laminate comprising 30.0 to 59.99 mass% of an amide group-containing monomer (A), 40.0 to 69.99 mass% of an aliphatic hydrocarbon group-containing monomer (B), and 0.01 to 10.0 mass% of a phosphate ester group-containing monomer (C).
Citation Information
Patent Citations
Photo-setting resin composition
JP1996092340A
Radiation-curable resin composition
JP1999100419A
Adhesive resin composition and binding material using the same
JP2009114352A
Adhesive resin composition, and adhesive material using the same
JP2009155387A
Radical curable resin composition, adhesive composition for motor
JP2017186439A